Mitigation of ice-induced vibrations for wind turbine foundation using damping vibration isolation - Baofeng, Zhang; Rui, Dong; Gang, Wang; Guojun, Wang; Dayong, Zhang (Frontiers in Materials, 2023)
As the single pile offshore wind power foundation is a typical flexible structure, the interaction between ice and structure will cause strong vibrations, which will have a significant impact on the normal operation of the upper motor and the safety of the foundation structure. The problems of ice-induced vibration have not been well resolved, one reason is that the dynamic interaction between ice and structure is complex that the practical ice loads have not been developed. Beads on the full scale of the interaction between ice and offshore platform in Bohai Sea, the strategy of mitigation of ice-induced offshore wind turbine foundation vibration was discussed. Through the simplified mechanical model of damping vibration isolation system, the relationship between the parameters of the damping isolation layer and the structural damping ratio was analyzed. Finally, the ANSYS numerical simulation method was used to discuss the wind turbine foundation structure’s vibration reduction effect under typical ice conditions and optimize the design parameters of the device.